The European central banks and its (un)conventional monetary policy - Černohorská, Liběna; Kula, Vojtěch (ISMA University, 2016)
The banking system in the European Union is unique in that there is a European Central Bank, and national central banks and commercial banks in each country. These countries have renounced their jurisdiction over national monetary policies, which have been delegated to the ECB, which implements a specific monetary policy in a specific economic area. This group of central banks, through their representatives, creates and implements monetary policy in the Eurozone. The current monetary policy of the ECB is still directly related to the recent global mortgage crisis and implements unconvetional monetary policy.
Evropská centrální banka a její (ne)konvenční měnová politika
Keywords: central bank; ECB; monetary policy; Eurozone; unconvential monetary policy; centrální banka; ECB; Eurozóna; měnová politika; nekonvenční měnová politika